Selenium (Geneva, 1987)
A richly detailed analysis of the many research issues surrounding the role of selenium as both an essential and a toxic element. The book opens with an analysis of what is known about the distribution of this ubiquitous element in the environment, including the natural presence of selenium in the food chain. Since food constitutes the main route of exposure for the general population, the book provides especially extensive coverage of levels typically found in different foods and the factors that can account for unusually high or low concentrations. Other sections cover the metabolism of selenium, discuss diseases in farm animals linked to either excessive or deficient intake, and summarize the results of experimental work on the physiological responses to toxicity and deficiency. Particular attention is given to the evaluation of past studies claiming a carcinogenic effect and more recent studies suggesting a protective effect against certain cancers in experimental animals.